2005
DOI: 10.1080/10976640500287703
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Calculation for Clinical Trials Using Magnetic Resonance Imaging for the Quantitative Assessment of Carotid Atherosclerosis

Abstract: In vivo MRI is capable of quantifying plaque volume and plaque composition, such as %lipid-rich/necrotic core and %calcification, in the clinical setting of a multi-center trial with low inter-scan variability. This study provides the basis for sample size calculation of future MRI trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 25 publications
10
92
0
4
Order By: Relevance
“…A number of studies have shown that MRI can accurately quantify vessel wall dimensions of atherosclerotic arteries in vivo (4), with measurement errors ranging from 4-6% for the lumen and wall, and 3.3% for total vessel area measurement (5,6). Thus, MRI provides a promising tool to study plaque progression and the remodeling process of atherosclerosis in humans in a non-invasive fashion.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown that MRI can accurately quantify vessel wall dimensions of atherosclerotic arteries in vivo (4), with measurement errors ranging from 4-6% for the lumen and wall, and 3.3% for total vessel area measurement (5,6). Thus, MRI provides a promising tool to study plaque progression and the remodeling process of atherosclerosis in humans in a non-invasive fashion.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the carotid wall volume might be a more reliable parameter of atherosclerosis burden when comparing across MR techniques. However, in a follow-up study using the 2D technique only, Mani et al found better reproducibility for W/OW than for wall volume, and W/OW has other advantages in clinical studies, such as the ability to meaningfully compare scans with differing numbers of slices (27).…”
Section: Discussionmentioning
confidence: 99%
“…From these models, lumen volume, wall volume, and total vessel volume were derived for the imaged volume (40 mm of longitudinal coverage). The total wall volume was also expressed as a percentage of the total vessel volume (wall/outer wall or W/OW ratio), as previously described (27).…”
Section: Image Analysismentioning
confidence: 99%
“…In this study, the PWV was used to measure the plaque burden because it can fully exploit the 3D data acquisition inherent in carotid MR imaging and is the most reproducible parameter to evaluate plaque burden among all the morphologic measurements by MR imaging. 23,24 Similarly, a previous study has shown that carotid plaque burden as measured by sonographic intima-media thickness is associated with recurrence of cardiovascular events including stroke. 25 Additionally, we found that there was no significant difference in the prevalence of carotid lumen stenosis of Ͼ50% between the 2 patient groups, indicating that the degree of arterial stenosis alone is a relatively poor predictor of recurrent neurologic events.…”
Section: Discussionmentioning
confidence: 99%